USE OF ASPARTIC ACID RACEMIZATION AND POST-BOMB 14C TO RECONSTRUCT GROWTH RATE AND LONGEVITY OF THE DEEP-WATER SLIT SHELL ENTEMNOTROCHUS ADANSONIANUS - Goodfriend G.A.; Kashgarian M.; Harasewych M.G. (My University, 1995)
Slit shells are living fossils which inhabit the continental slope. Aspartic acid racemization in the nacreous layer of the slit shell Entemnotrochus adansonianus is shown to occur at a remarkably high rate, sufficient to provide annual resolution of the ages of samples taken along the growth spiral of the shells, thus providing information on growth rates and longevity. Calibration of the racemization rate was obtained by 14C analysis of a post-bomb specimen. The form of the racemization curve was determined by a heating experiment at 60°C; a cubic transformation of the D/L values was found to be linear with respect to time. In these specimens in which a detailed series of samples was analyzed, juvenile growth was found to be very rapid and adult growth 1-2 orders of magnitude slower; adulthood is reached in 2-4 years. Analysis of lip and apical samples of additional shells (total n = 9) shows that individuals reaching adulthood have life spans averaging six years (maximum: 14 yr). The life histories of these deep-water gastropods are thus similar to littoral taxa. Analysis of the prismatic layer shows that this racemizes at a much slower rate than the nacreous layer.